Efficacy and safety of topical BAK-free travoprost 0.004% versus BAK-preserved travoprost 0.004% in the treatment of primary open angle glaucoma: a comparative study at a tertiary care hospital - C. R., Jayanthi; R. N., Divyashree; B. L., Sujatha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Prostaglandin analogues (PGAs) reduce intraocular pressure (IOP) in patients with primary open-angle glaucoma (POAG); however, these medications may affect the ocular surface and elicit ocular discomfort when preserved with benzalkonium chloride (BAK). Hence the above study was taken to evaluate the benefit of BAK-free formulations of travoprost. The objectives of the study were to compare the efficacy, safety of topical BAK-free travoprost 0.004% versus BAK-preserved travoprost 0.004% in patients with primary open angle glaucoma. Methods: 40 patients with POAG who fulfilled the inclusion /exclusion criteria were randomised into two groups of 20 each to receive BAK-free travoprost 0.004% or BAK-preserved travoprost once daily in the evening. Efficacy was measured in terms of reduction in IOP monitored at 4, 8 and 12 weeks from baseline. Ocular surface disease index (OSDI) questionnaire was used to assess the ocular surface symptoms. Safety was assessed by monitoring treatment emergent adverse drug reactions (ADRs). Results: Both the study medications were effective in reducing IOP when compared to baseline. Mean IOP reduction from baseline to week 12 was 11±3mmHg (p <0.001), 10.78±3.01mmHg, (p<0.001) in BAK-free travoprost and BAK-preserved travoprost groups respectively. Both produced equivalent reductions in IOP at the end of 4 (7.89±1.82 vs 7.63±2.83, p=0.72), 8 (9.94±2.75 vs10.05±2.75, p=0.90), and 12 weeks (11±3 vs10.78±3.01, p=0.82). BAK-free travoprost demonstrated significantly lower OSDI scores (15.10±3.60) compared to BAK- preserved travoprost (23.47±7.10) at 12 weeks (p <0.0001). There was no significant difference in occurrence of conjunctival hyperaemia between the study drugs (c2 = 0, df = 1, p = 1) and BAK-free travoprost was well tolerated. Conclusions: BAK-free and BAK-preserved travoprost significantly reduced IOP at 12 weeks. But, BAK- free travoprost produced significantly less ocular surface symptoms as compared to BAK- preserved travoprost. Hence it could be a favourable option in POAG patients with ocular surface disease symptoms.